Crocidolite in the districts of Prieska and Hay - Schoeman, H E (Rhodes University, Faculty of Science, Department of Geology, 1930)
From Introduction: The belt of hilly country extending from the southern extremity of the Doornbergen, through Prieska, Niekerkshoop, Griquatown and Kuruman, to a point far north or the latter, constitutes a region or great scientific and economic interest. Spoken of generally as the "Blue Asbestos Belt" , it has ramifications stretching in north, and north-westerly directions from Prieska. In the south it is known as the Doornbergen, passing into the "Asbestos Mountains" north of the Orange River, while farther north it becomes the Kuruman Hills. This large area is unique in that enormous deposits of fibrous crocido1ite or "blue asbestos" are known to occur scattered more or less irregularly over the entire belt. The mineral, often accompanied by some or all of its variations and alteration products, has been reported from nearly every farm, excepting only that portion covered by Ongeluk Volcanics, and the UPPER BEDS OF THE LOWER GRIQUATOWN SERIES, which thus form the only interruption to an otherwise unbroken extension of crocidolite bearing strata.
Keywords: Uncatalogued